The Gangs of Bangladesh Mastaans, Street Gangs and ‘Illicit Child Labourers’ in Dhaka - Atkinson-Sheppard, Sally (Palgrave Advances in Criminology and Criminal Justice in Asia, 2019)
XII, 203 p. 3 illus.